A Class of DBDF Methods with the Derivative Modifying Term (Journal of Computational Mathematics, 2018)
In this paper, a class of DBDF methods with the derivative medifying term is presented. The methods is $$\sum\limits^k\limits_{j=0}a_jy_{n+j}=hf_{n+k}+ah^2f'_{n+k}$$ which is of $k$-step and order $k+1$. The numerical stability of the new method is much better than both Gear's methods and Enright's methods.